Annual Plan 2006-2007 Volume I Government of Uttar Pradesh - Planning Commission (Planning Commission, 2005)
With the formulation of Annual Pan 2006-07. we are entering the last year of Tenth Five Year Plan (2002-07). Though after independence the State has made considerable progress during the ten Five Year Plan periods, yet much more remains to be done for ensuring better quality of life. In a democratic set up, the government is required to move ahead ceaselessly and constantly on the development path. In fact the process of development never ends. It has been rightly said that it is better to travel hopefully than to arrive. This is true for the process of development.
Government of Uttar Pradesh, State Planning Commission